Analisis literasi keuangan, pendapatan dan persepsi risiko terhadap keputusan investasi serta perilaku keuangan sebagai variabel intervening - Mega Lestari; Dewi Cahyani Pangestuti; Ardhiani Fadila (LPMP Imperium, 2022)
The purpose of this study was to determine the effect of financial literacy, income, and risk perception on investment decisions through financial behavior as an intervening variable in the workforce aged 20 - 30 years in the Medan Satria village area. The sample size used was 94 respondents using non-probability sampling method, especially purposive sampling technique. Data collection was done by distributing questionnaires via google form. The analysis technique used is PLS (Partial Least Square) analysis through the Smart PLS 3 program. The results show (1) financial literacy has a significant positive effect on investment decisions, (2) income has a significant negative effect on investment decisions, (3) perception of risk has a significant positive effect on investment decisions. significant positive effect on investment decisions, (4) financial literacy has a significant positive effect on financial behavior, (5) income has a significant positive effect on financial behavior, (6) perception of risk has a significant positive effect on financial behavior, (7) financial literacy has a significant negative effect on investment decisions through financial behavior, (8) income does not have a significant positive effect on investment decisions through financial behavior, (9) risk perception does not have a significant positive effect on investment decisions through financial behavior.